S1 Progressive pulmonary fibrosis: top ten research priorities. (11th November 2022) - Fabbri, L; Cowan, K; Adams, W; Conway, J; Jones, S; Wright, L; Chaudhuri, N; Russell, AM; Gibbons, MA; Hart, S; Lynch-Wilson, J; Jenkins, GR
Abstract : Introduction and Objectives: The term progressive pulmonary fibrosis (PPF) encompasses a group of diseases affecting more than 35, 000 people in the United Kingdom. 1 PPF is characterised by fibrotic remodelling of the lung parenchyma, leading to relentless progression and poor prognosis. No cure is available. This study aimed to identify stakeholders' research priorities regarding diagnosis, treatment, and management of PPF patients, to inform research funders and national policymakers in their strategies to support funding priorities in PPF. Methods: A James Lind Alliance Priority Setting Partnership (PSP) for PPF was convened in 2020. A steering group of patients, carers, and healthcare professionals (HCPs) with expertise in PPF met 11 times over two years and led the PSP. Stakeholders' questions and uncertainties about PPF were gathered through an open online survey, advertised on social media and postal services through the support groups network, and word of mouth. Following thematic analysis, responses were coded to identify overarching themes, from which summary research questions were generated. A comparative literature review identified unanswered research questions, which were shortlisted by stakeholders through a second online survey. Subsequently, the 15 highly top-rated questions were ranked during a 2-day online workshop to select the top 10. Workshop participants were purposively selected to represent the different stakeholders and guarantee adequate expertise and geographical distribution. Results: The initial online survey had 638 responses, generating 2542 single statements that were distilled into 48 thematic research questions. Participants were represented by 57% people living with PPF, 25% carers, and 15% HCPs. After evidence review, 44 questions were included in the second survey and shortlisted by 834 stakeholders (51.4% people living with PPF, 32.7% carers, and 15.8% HCPs). After three rounds of discussions, workshop participants ranked and defined the top 10 priority list ( table 1 ). Conclusions: Stakeholders consider that early diagnosis, new treatment, symptom management, and quality of life are key priority areas that require prioritisation of funding and research. Reference: Snell N, et al. P272 Epidemiology of idiopathic pulmonary fibrosis in the UK: findings from the British lung foundation's 'respiratory health of the nation' project. Thorax 2016;71 :A236-A236.